Ultrasound-Guided Inferior Alveolar Nerve Block in the Horse: Assessment of the Extraoral Approach in Cadavers. (March 2019) - Johnson, Jessica Purefoy; Peckham, Robert Karl; Rowan, Conor; Wolfe, Alan; O'Leary, John Mark
Blinded techniques to desensitize the inferior alveolar nerve (IAN) include intraoral, angled, and vertical extraoral approaches with reported success rates of 100%, 73%, and 59%, respectively. It has not been determined whether an ultrasound-guided extraoral approach is feasible. Further, the fascicular nature of the inferior alveolar and lingual nerves of the horse has not been described. The objectives of this study were to describe a low-volume ultrasound-guided vertical extraoral inferior alveolar nerve block technique and to describe the fascicular nature of these nerves. An ultrasound-guided approach to the IAN was conducted with a microconvex transducer and an 18-G, 15-cm spinal needle using a solution containing iodinated-contrast and methylene blue dye. Accuracy was assessed by contrast visualized at the mandibular foramen on computed tomography (CT) and methylene blue dye staining of the nerves on gross dissection. Sections of inferior alveolar and lingual nerves were submitted for histological analysis. Assessment by CT and dissection determined success rates of 81.3% and 68.8%, respectively; 68.8% of injections had inadvertent methylene blue dye staining of the lingual nerve. Nerve histology revealed both the inferior alveolar and lingual nerves to be multifascicular in nature. Mean fascicle counts for the inferior alveolar and lingual nerves were 29 and 30.8, respectively. The technique is challenging and no more accurate than previously published blinded techniques. Any extraoral approach to the IAN is likely to also desensitize the lingual nerve.